PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN, Dan KARAKTERISTIK TENAGA PEMASAR TERHADAP MOTIVASI DAN KINERJA TENAGA PEMASAR PADA PT. BANK RAKYAT INDONESIA (Persero) Tbk. CABANG JOMBANG - Pradita, Mochamad Yanuar (Faculty of Economics and Business, University of Muhammadiyah Malang, 2016)
The purpose of this study was to determine: 1) the effect of compensation, the influence of leadership styles, influences the characteristics of marketers on work motivation, 2) the effect of work motivation, the effect of compensation, the influence of the characteristics of marketers to performance marketers, 3) the effect of compensation, the influence of leadership style , the effect on the performance characteristics of the sales force through a sales force motivation. This research is quantitative descriptive. The population of this research is all marketers in PT Bank Rakyat Indonesia (Persero) Tbk. Jombang branch sales force numbering 170 persons, comprising 136 personnel and 34 micro marketers of retail sales force. Samples are 136 respondents taken by purposive sampling technique. Data collection techniques are questionnaires, interviews, and documentation. Data analysis techniques performed by SEM analysis.Keywords: Brand Positioning, Consumption Values, Consumer Choice Behavior,SEM-PLS, Telecommunication.